The Role of Influencers and Digital Content as a Marketing Strategy During the Covid-19 Pandemic - Fitria Haqsari Ratnapertiwi; Az-Zein Hafizd; Putri Sheila Febriani (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
One of the impacts felt by entrepreneurs during the Covid-19 pandemic was the decline in the economy and business. In this modern era, social media has become a basic need for society. Therefore, business people must optimize digital marketing strategies. One way that is considered the most effective is using the services of an influencer. The purpose of this research is to find out how big the role of influencers and digital content is in increasing a business. This type of research is narrative qualitative research and data collection method by interview. The results of this study are entrepreneurs admit that influencers and digital content are very influential on their online business. Especially during the covid 19 pandemic like now, both in terms of turnover and followers.